Adoption of Improved Wheat Farming Practices Among the Farmers of Surkhet District, Nepal - Aryal, Bishnu Prasad (1987)
The main purpose of the study was to determine the adoption of improved wheat farming practices among the farmers of Surkhet district, Nepal. The study also attempted to identify the farmers' reasons for not adopting these practices as well as to determine the relationship between adoption and their selected personal characteristics. The respondents of the study consisted of 120 farmers which were randomly selected from nine wards of the district. The data were collected by means of personal interview.